Public journalism and professional culture - Ruusunoksa, Laura (Javnost (Ljubljana), 2006)
This article provides an insight into the public journalism discussion and offers a way of understanding how journalists at local, regional and national levels interpret and practise public journalism slightly differently. Journalists' interpretations of participatory public journalism initiatives in three Finnish newspapers from local, regional and national public spheres are used as a point of departure for discussing professionalism in journalism. The paper argues that professionalism offers a way to articulate journalists' relations to the market, administration and the public in different ways in different public spheres.
Keywords: javnost; javna sfera; novinarji; novinarstvo; journalism; profesionalizem